No Promotion of Marriage in TANF! - Fineman, Martha (Social justice, 2003)
Part of a special issue on applied research and social justice. The text is provided of a position paper outlining the reasons for opposing the welfare marriage promotion provision of the bill (HR 4) to reauthorize the Temporary Assistance to Needy Families (TANF) program, passed by House Republicans on February 13, 2003. It is argued that the TANF reauthorization bill promotes marriage as a way of addressing poverty, violating women's rights and diverting valuable resources in the process.